Family and friends in eighteenth-century England: Household, kinship, and patronage - Tadmor, Naomi (Cambridge University, 2013)
Naomi Tadmor presents a new description of how family structures operated in eighteenth-century England starting from an analysis of contemporary language (in diaries; conduct treatises; novels by Richardson and Haywood; and other sources). Her book will be of great interest to historians and literary scholars of the period.